2023
DOI: 10.21873/cdp.10220
|View full text |Cite
|
Sign up to set email alerts
|

Is the Routine Histopathologic Diagnosis of Ulcerative Colitis Based on Cross-cut Sections or on Well-oriented Sections?

Abstract: ackground/Aim: For many years, it was empirically estimated that the majority of the routine colon biopsies in Swedish patients with ulcerative colitis (UC), exhibited cross-cut crypts. The aim of the present study was to assess the frequency of cross-cut crypts (CCC) and well-oriented crypts in routine colon biopsies in German patients with UC. Patients and Methods: In total, 447 colon biopsies: 376 with UC and 71 controls were investigated. Results: Out of 376 colon biopsies with UC, 73% exhibited ≥60% CCC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…A series of studies, mainly conducted by Rubio and coworkers, has underlined the importance of crypt asymmetrical branching of regenerating crypts after chronic neutrophil-driven damage as an instrument for a more precise definition of crypt distortion [17,18]. Recently, the same group demonstrated that specimen orientation could represent a bias in crypt morphology evaluation; a significant portion of the histologic section that resulted in a diagnosis of IBD held cross-cut crypts, an inappropriate sectioning plane that modifies the correct assessment of the other histological parameters that defined the diagnosis of IBD [19][20][21]. On the other side, a series of cryptassociated anomalies were described in addition to crypt branching in crypt destructive inflammations that should be considered in their assessment on histologic slides [22].…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies, mainly conducted by Rubio and coworkers, has underlined the importance of crypt asymmetrical branching of regenerating crypts after chronic neutrophil-driven damage as an instrument for a more precise definition of crypt distortion [17,18]. Recently, the same group demonstrated that specimen orientation could represent a bias in crypt morphology evaluation; a significant portion of the histologic section that resulted in a diagnosis of IBD held cross-cut crypts, an inappropriate sectioning plane that modifies the correct assessment of the other histological parameters that defined the diagnosis of IBD [19][20][21]. On the other side, a series of cryptassociated anomalies were described in addition to crypt branching in crypt destructive inflammations that should be considered in their assessment on histologic slides [22].…”
Section: Discussionmentioning
confidence: 99%